2011
DOI: 10.1186/cc10466
|View full text |Cite
|
Sign up to set email alerts
|

Restrictive strategy of intraoperative fluid maintenance during optimization of oxygen delivery decreases major complications after high-risk surgery

Abstract: IntroductionOptimal fluid management is crucial for patients who undergo major and prolonged surgery. Persistent hypovolemia is associated with complications, but fluid overload is also harmful. We evaluated the effects of a restrictive versus conventional strategy of crystalloid administration during goal-directed therapy in high-risk surgical patients.MethodsWe conducted a prospective, randomized, controlled study of high-risk patients undergoing major surgery. For fluid maintenance during surgery, the restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(66 citation statements)
references
References 39 publications
6
51
0
6
Order By: Relevance
“…40 The basic premise of the GDFT consists of ensuring an optimal blood volume; the association of restrictive fluid therapy 41 with the identification of optimal preload or of those patients who increased their SV through a volume load (respondent to fluids) implies relative hypovolemia; the quick correction of this problem is essential to ensure correct tissue perfusion. This a priori should be faster with colloids, since, as demonstrated in healthy patients and animal models, the proportion of liquid required to achieve a goal of hemodynamic stabilization is 1:4 42 ; however, this cannot be confirmed by the data obtained in this meta-analysis nor can be demonstrated with recent studies specifically designed to determine it.…”
Section: Discussionmentioning
confidence: 99%
“…40 The basic premise of the GDFT consists of ensuring an optimal blood volume; the association of restrictive fluid therapy 41 with the identification of optimal preload or of those patients who increased their SV through a volume load (respondent to fluids) implies relative hypovolemia; the quick correction of this problem is essential to ensure correct tissue perfusion. This a priori should be faster with colloids, since, as demonstrated in healthy patients and animal models, the proportion of liquid required to achieve a goal of hemodynamic stabilization is 1:4 42 ; however, this cannot be confirmed by the data obtained in this meta-analysis nor can be demonstrated with recent studies specifically designed to determine it.…”
Section: Discussionmentioning
confidence: 99%
“…The study of Lobo et al [15] utilized a DO 2 goal similar to that of Pearse et al [13] above, for two groups; one with typical crystalloid 'maintenance' iv crystalloid (lactated Ringer's solution, 12 ml kg À1 h À1 ), the other with a considerably lower infusion rate (4 ml kg À1 h À1 ). Optimization of DO 2 I was continued throughout surgery and for the following 8 h. Both groups showed a reduced incidence of complications relative to earlier studies on a similar group of patients [16].…”
Section: Fluid Overload As a Confoundermentioning
confidence: 97%
“…Fluid overload has, however, been shown to be a real concern [14]. The study of Lobo et al [15] has addressed the problem, in particular, with regard to 'maintenance' intravenous (iv) crystalloid. It is important to avoid lumping crystalloid and colloid together simply as fluid, since crystalloid adds to all compartments, colloid principally, at least initially, to the circulatory volume.…”
Section: Fluid Overload As a Confoundermentioning
confidence: 98%
“…Clinical data on the effect of perioperative fluid management on the risk for PPCs during major abdominal surgery are extremely heterogeneous. In two recent prospective investigations a restrictive fluid management strategy was associated with a reduction in the overall complication rate, but the rate of PPCs did not differ among groups [75,76]. In a retrospective analysis of a large database, Blum et al [24 && ] identified a higher amount of intraoperative crystalloid infusion as a risk factor for the development of postoperative ARDS.…”
Section: Intravascular Volume Managementmentioning
confidence: 98%